To solve the partial fraction decomposition, we first factor the denominator:
X^2 - 3X + 1 = (X - φ)(X - ψ)
where φ and ψ represent the roots of the quadratic equation.
The roots of the quadratic equation can be found using the quadratic formula:
X = (-(-3) ± √((-3)^2 - 4(1)(1))) / (2(1))
= (3 ± √(5)) / 2
So, the roots of the quadratic equation are (3 + √5) / 2 and (3 - √5) / 2.
Therefore, the factored form of the denominator is:
(X + 2) (X - (3 + √5) / 2) (X - (3 - √5) / 2)
Now, let's write the partial fraction decomposition:
(X - 1)(X + 1) / ((X + 2)(X^2 - 3X + 1))
= A / (X + 2) + (B(X - (3 + √5) / 2) + C(X - (3 - √5) / 2)) / (X^2 - 3X + 1)
To find the values of A, B, and C, we can multiply both sides of the equation by the denominator:
(X - 1)(X + 1) = A(X^2 - 3X + 1) + (B(X - (3 + √5) / 2) + C(X - (3 - √5) / 2))(X + 2)
Expanding the equation and combining like terms, we get:
X^2 - 1 = A X^2 + (-3A + B + C) X + (A + (2B - (3 + √5) / 2) + (2C - (3 - √5) / 2))
Now, we need to match the coefficients of the corresponding powers of X on both sides of the equation.
For X^2:
A = 1
For X^1:
-3A + B + C = 0
For X^0:
A + (2B - (3 + √5) / 2) + (2C - (3 - √5) / 2) = -1
Simplifying the equations, we have:
A = 1
-3 + B + C = 0
2B + 2C - 3 + √5 - 3 - √5 = -1
Simplifying further:
B + C = 3
2B + 2C - 6 = -1
2B + 2C = 5
Simplifying again:
B + C = 3
B + C = 2.5
We have two conflicting equations, which means there is no solution for this partial fraction decomposition.
Solve the partial fraction (X-1)(X+1)/(X+2)(X^2-3X+1).
3 answers
(x-1)(x+1)/((x+2)(x^2-3x+1))
= 3/(11(x+2)) + (8x-7)/(11(x^2-3x+1))
= 3/(11(x+2)) + (8x-7)/(11(x^2-3x+1))
I apologize for the mistake in my previous response. You are correct, the partial fraction decomposition of (x-1)(x+1)/((x+2)(x^2-3x+1)) can be written as:
(x-1)(x+1)/((x+2)(x^2-3x+1)) = 3/(11(x+2)) + (8x-7)/(11(x^2-3x+1))
This can be obtained by finding the values of A, B, and C through a similar process as previously described.
(x-1)(x+1)/((x+2)(x^2-3x+1)) = 3/(11(x+2)) + (8x-7)/(11(x^2-3x+1))
This can be obtained by finding the values of A, B, and C through a similar process as previously described.